[Letter, 1874 Nov. 19] Fort Sampson, Mackenzie River, North West Territory of Canada [to] the Rev. the Secretaries, Church Missionary Society [London] - Allabasca, W. (Adam Matthew Digital, 1874)
Ms. letter describing the routines of missionary work amongst Native Americans, and a list of requests for the Church Missionary Society in England